Two rare cases of benign struma ovarii with malignant recurrence - Kanella Kantreva; Stavroula A Paschou; Katerina Stefanaki; Kanella Pappa; Paraskevi Kazakou; Dionysios Vrachnis; Evangelia Kavoura; Kitty Pavlakis; Eirini Giovannopoulou; Konstantinos Lathouras; Maria Alevizaki; Katerina Saltiki (Endocrinology, Diabetes & Metabolism Case Reports, 2024)
Struma ovarii is an ovarian teratoma that comprises 2–5% of all ovarian teratomas. Malignant transformation of struma ovarii occurs in less than 5% of all cases, and metastatic disease is even rarer. We report two cases initially diagnosed with benign struma ovarii that presented malignant transformation, specifically highly differentiated follicular carcinoma of the ovary (HDFCO), some years after the first diagnosis. Case 1 concerns a 37-year-old female featuring HDFCO of the right ovary with multiple metastatic foci, who was diagnosed with benign struma ovarii 14 years ago. Case 2 concerns a 26-year-old female diagnosed with HDFCO of the left ovary. This patient was initially diagnosed with benign struma ovarii 6 years ago that recurred 4 years after the diagnosis. Both patients were treated with surgery, adjunctive total thyroidectomy, and radioactive iodine (131I) therapy.